1, 1-Disubstituted-2-vinylcyclopropanes for the synthesis of amphiphilic polymers. (May 2015) - Seuyep Ntoukam, Denis H.; Jiworrawathanakul, Suchaya; Hoven, Voravee P.; Luinstra, Gerrit A.; Theato, Patrick
Graphical abstract: Highlights: Synthesis of zwitterionic and non-ionic polymer amphiphiles. Polymerization of 1, 1-disubstituted-2-vinylcyclopropanes. Sequential post-polymerization modification. Pentafluorophenyl ester conversion with amines. Abstract: Two 1, 1-disubstituted-2-vinylcyclopropane monomers, namely 1-aceto-1-pentafluorophenoxycarbonyl-2-vinylcyclopropane and 1-dodecanoxycarbonyl-1-pentafluorophenoxycarbonyl-2-vinylcyclopropane containing activated pentafluorophenyl esters, were polymerized by free radical ring opening polymerization. The obtained reactive polymers were then employed for the synthesis of non-ionic and zwitterionic polymeric surfactants via sequential post-polymerization modifications.